2020
DOI: 10.1101/2020.11.11.20229526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Universal Health Coverage and COVID-19 Pandemic: A Bangladesh Perspective

Abstract: BackgroundLike many other countries around the world, Bangladesh adopts Universal Health Coverage (UHC) as a national aspiration. The central theme of its providing quality and affordable health services which is a significant element of social protection. This paper was aimed to provide a narrative understanding of the perspectives of UHC in Bangladesh towards COVID-19 based on the existing literature.MethodsWe conducted a review combining articles and abstracts with full HTML and PDF format. We searched Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The current research also revealed that 97.4% of respondents agreed that the COVID-19 incubation time ranges from 2 to 14 days. The research conducted by also found that knowledge of the incubation time was successful and similar (91.3 percent) (Ferdous & Islam, 2020). In the study by Zhong et al (2020), the majority of participants (96.4 %) had not recently visited a busy area.…”
Section: Discussionmentioning
confidence: 75%
“…The current research also revealed that 97.4% of respondents agreed that the COVID-19 incubation time ranges from 2 to 14 days. The research conducted by also found that knowledge of the incubation time was successful and similar (91.3 percent) (Ferdous & Islam, 2020). In the study by Zhong et al (2020), the majority of participants (96.4 %) had not recently visited a busy area.…”
Section: Discussionmentioning
confidence: 75%
“…12 Shortages of health-care workers and personal protective equipment and other capacity constraints limited the ability of health systems to maintain essential services. 13 , 14 , 15 , 16 Administrative data have shown that millions fewer vaccinations occurred in 2020 as compared with 2019, and disruptions to other maternal and child health services in 2020. 17 , 18 , 19…”
Section: Introductionmentioning
confidence: 99%